Microglia depletion/repopulation does not affect light-induced retinal degeneration in mice - Laudenberg, Nils; Kinuthia, Urbanus Muthai; Langmann, Thomas (Frontiers in Immunology, 2024)
Reactive microglia are a hallmark of age-related retinal degenerative diseases including age-related macular degeneration (AMD). These cells are capable of secreting neurotoxic substances that may aggravate inflammation that leads to loss of photoreceptors and impaired vision. Despite their role in driving detrimental inflammation, microglia also play supporting roles in the retina as they are a crucial cellular component of the regulatory innate immune system. In this study, we used the colony stimulating factor 1 receptor (CSF1R)-antagonist PLX3397 to investigate the effects of microglia depletion and repopulation in a mouse model of acute retinal degeneration that mimics some aspects of dry AMD. Our main goal was to investigate whether microglia depletion and repopulation affects the outcome of light-induced retinal degeneration. We found that microglia depletion effectively decreased the expression of several key pro-inflammatory factors but was unable to influence the extent of retinal degeneration as determined by optical coherence tomography (OCT) and histology. Interestingly, we found prominent cell debris accumulation in the outer retina under conditions of microglia depletion, presumably due to the lack of efficient phagocytosis that could not be compensated by the retinal pigment epithelium. Moreover, our in vivo experiments showed that renewal of retinal microglia by repopulation did also not prevent rapid microglia activation or preserve photoreceptor death under conditions of light damage. We conclude that microglia ablation strongly reduces the expression of pro-inflammatory factors but cannot prevent photoreceptor loss in the light-damage paradigm of retinal degeneration.